Organophosphate Ester Flame Retardants: Are They a Regrettable Substitution for Polybrominated Diphenyl Ethers? - Blum, Arlene (Environ Sci Technol Lett, 2019)
As the use of polybrominated diphenyl ethers (PBDEs), and the entire class of organohalogen flame retardants, is declining, the use of organophosphate esters flame retardants (OPFRs) is increasing. In this paper, we ask whether OPFRs are a better choice than PBDEs. To address this question, we compared OPFRs with PBDEs for a wide range of properties. OPFRs exposure is ubiquitous in people and in outdoor and indoor environments, and are now often found at higher levels compared to PBDE peak exposure levels. Furthermore, data from toxicity testing, epidemiological studies, and risk assessments all suggest that there are health concerns at current exposure levels for both halogenated and non-halogenated OPFRs. Obtaining the scientific evidence needed for regulation of OPFRs can take many years. Given the large number of OPFRs in use, manufacturers can move towards healthier and safer products by developing innovative ways to reduce fire hazard for electronics enclosures, upholstered furniture, building materials and other consumer products without adding flame retardant chemicals.